CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

What should be subtracted from 3m2n + 5mn2 - 2m2n2 to get -3m2n + 7mn2 + 4m2n2 ?


Solution

Let px be subtracted from 3m2n+5mn2-2m2n2 to get -3m2n+7mn2+4m2n2.3m2n+5mn2-2m2n2 -px=-3m2n+7mn2+4m2n2px=3m2n+5mn2-2m2n2 --3m2n+7mn2+4m2n2px=3m2n+5mn2-2m2n2 +3m2n-7mn2-4m2n2px=3m2n+3m2n+5mn2-7mn2-2m2n2 -4m2n2px=6m2n-2mn2-6m2n26m2n-2mn2-6m2n2 can be subtracted from 3m2n+5mn2-2m2n2  to get -3m2n+7mn2+4m2n2.

Mathematics
Mathematics (Algebra)
Standard IX

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
Same exercise questions
View More



footer-image